Smoking and ulcer perforation. Issue 2 (1st August 1997) - Svanes, C; Søreide, J A; Skarstein, A; Fevang, B T; Bakke, P; Vollset, S E; Svanes, K; Søreide, O
Abstract : Background —The use of ulcerogenic drugs is the only well documented risk factor for peptic ulcer perforation, but accounts for only a quarter of the events. Smoking is a well known risk factor for uncomplicated ulcer disease, and patients with ulcer bleeding have increased death rates from smoking related disorders. Aim —To assess the role of smoking in ulcer perforation. Subjects —A total of 168 consecutive patients with gastroduodenal ulcer perforation and 4469 control subjects from a population based health survey. Methods —The association between ulcer perforation and smoking habits was analysed by logistic regression while adjusting for age and sex. Results —Current smoking increased the risk for ulcer perforation 10-fold in the age group 15–74 years (OR 9.7, 95% CI 5.9 to 15.8) and there was a highly significant dose-response relationship (p<0.001). The results were similar in men (OR 9.3, 95% CI 4.9 to 17) and women (OR 11.6, 95% CI 5.3 to 25), and for gastric (OR 10.5, 95% CI 4.5 to 25) and duodenal (OR 8.6, 95% CI 4.9 to 15.4) ulcer perforation. No increase in risk was found in previous smokers (OR 0.8, 95% CI 0.2 to 2.2). Conclusion —Our findings suggest that smoking is a causal factor for ulcer perforation and accounts for a major part of ulcer perforations in the population aged less than 75 years.